Knowledge and utilization of preventive measures in the control of neonatal malaria in south-eastern Nigeria - Chukwuocha, Uchechukwu M.; Nwakwuo, Geoffrey C.; Alinnor, Lawrence O. (Tanzania Journal of Health Research, 2016)
Background: The burden of neonatal malaria remains a major public health problem in Nigeria receiving less attention. Knowledge and awareness of preventive measures of neonatal malaria is still very low. This study aimed at assessing the Knowledge and utilization of preventive measures in the control of neonatal malaria in South-eastern Nigeria. Methods: Structured pretested questionnaires were used to collect data from 230 consenting pregnant women attending antenatal clinics in the Federal Medical Centre, Owerri, Nigeria. These women were followed up until delivery and blood samples were taken from their new born for malaria parasite tests. Using SPSS, qualitative variables were summarized with proportions and chi-square test was used to investigate associations between qualitative variables. Results: There was high level of awareness on the use of malaria preventive measures by pregnant women in the control of neonatal malaria. A significant relationship between the use of malaria preventive measures and neonatal malaria was also shown. Over three-quarters (79.7%) of women had knowledge of malaria preventive measures during pregnancy. Use of anti-malarial prophylaxis (91.8%) followed by the use of insecticide treated nets (ITNs) (49.5%) were practiced. ITNs were less (19.6%) used during pregnancy. Most of them (57.8%) received single dose of intermittent preventive treatment (IPT) using sulphadoxine-pyrimethamine during pregnancy, while 37% received two doses of IPT. Conclusion: More effort need to be made and support provided to women during pregnancy to encourage usage of preventive measures. There is also need to develop a health promotion package to eliminate factors discouraging the use of specific preventive measures like IPTp and ITNs.